2011
DOI: 10.4315/0362-028x.jfp-11-009
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Examination of Nonheated Foods Served in Feeding Programs of Elementary Schools, Iksan City, Jeonbuk Province, Korea

Abstract: More than 90% of elementary school students in Korea have lunch provided by a school feeding program. This study examined nonheated foods, foods in which final ingredients were added after cooking ("heated/nonheated foods"), and desserts for microbial contamination levels and the presence of foodborne pathogens. We obtained a total of 77 food samples belonging to the above three groups from four elementary schools located in Iksan, Jeonbuk, Korea, from June to July 2010. Among the samples, 15% of nonheated foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
0
7
1
Order By: Relevance
“…In the present study, APC numbers of tested SVF samples were near those reported in Korean elementary schools, which indicated that 15% of nonheated foods and 9% of heated/nonheated food samples were not meet food standards (Ryu et al, 2011…”
Section: Microbial Analysis Of Svf Samplescontrasting
confidence: 47%
“…In the present study, APC numbers of tested SVF samples were near those reported in Korean elementary schools, which indicated that 15% of nonheated foods and 9% of heated/nonheated food samples were not meet food standards (Ryu et al, 2011…”
Section: Microbial Analysis Of Svf Samplescontrasting
confidence: 47%
“…2). In Korean schools Ryu et al (2011) reported of the provision of a variety of side dishes and desserts with the main meal in schools. This was not present in the schools in Ashanti Region.…”
Section: Sources Of Meals For Students In Shs In Ashanti Region and Fmentioning
confidence: 99%
“…Meldrum et al (2009) reported of a relatively safer ready-to-eat meals in schools in Wales as there were no microbiologically unacceptable food. The schools in Wales had HACCP in place whilst in Korea, the microbiological quality of school meals sampled were reported not to be adequate to ensure food safety (Ryu et al, 2011) hence the high rate of FBD from schools in the country. order to provide safe food for students.…”
Section: Fig 3 Shs Boarding Students Recommended Improvements In Ghmentioning
confidence: 99%
See 2 more Smart Citations